PENGARUH LOKASI DAN FASILITAS TERHADAP KEPUASAN PENGUNJUNG WISATA AIR PANAS PACET DI KABUPATEN MOJOKERTO - Mariana, Dewi; Novaria, Rachmawati; Nasution, Ute Chairuz (Jurnal Dinamika Administrasi Bisnis, 2018)
The research entitled "Effect Of Location And Facilities To Satisfaction Visitor Tourist Pacet Hot Water In Mojokerto Regency". This study aims to determine the effect of Location and Facilities on Visitor Satisfaction and to know the dominant influence between Location and Facilities to Satisfaction of Pacet Hot Water Tour Visitors in Mojokerto Regency.               The population in this research is Pacet hot water tour visitor in Mojokerto regency. Data collection method used is questionnaire with 100 respondents. The type of research used is quantitative research, the method of analysis used is the analysis of description and multiple linear regression analysis.               Based on the result of the research, there are multiple linear equations Y = 5.064 + 0.334X1 + 0.245X2 + e using SPSS 16, F hypothesis shows F count = 88.368 with significant value = 0.000 <0.05 the meaning "that all independent variables (Location and Facilities) significantly influence the dependent variable (Y) " While the partial hypothesis test (t test) obtained t arithmetic from the location variable of 4.388 and the facility variable of 3.527 where the probability is smaller than 0.05 then the hypothesis accepted. From multiple linear regression analysis it can be seen that the most dominant variable is location variable (X1) with beta coefficient value of 0.334 Keywords: Location, Facilities, Visitor Satisfaction